Experimental and numerical investigations on concrete filled carbon FRP tube (CFRP-CFFT) columns manufactured with ultra-high-performance fibre reinforced concrete. (1st May 2020) - Fang, C.; Mohamed Ali, M.S.; Sheikh, A.H.
Abstract: This study aims to investigate the structural responses of five concrete filled carbon FRP tube (CFRP-CFFT) columns manufactured with ultra-high-performance fibre reinforced concrete (UHPFRC) under concentric or eccentric loading protocols with eccentricities ranging from 0.067D (depth) to 0.57D (depth). One CFRP-CFFT UHPFRC beam with the same cross-section configuration used for columns was subjected to four-point flexural bending. Furthermore, finite element (FE) analysis incorporating concrete damage plasticity (CDP) model was also conducted to simulate the behaviours of CFRP-CFFT UHPFRC members; the corresponding load-axial displacement and load-lateral deflection relationships were numerically generated to compare with the experimental results. FE simulations exhibit a high correlation compared to experimental results, which further highlights the applicability of FE modelling in predicting the structural response of the CFRP-CFTT UHPFRC members. A load-moment ( P - M ) interaction envelope was generated from the FE modelling to facilitate the development of a design guideline of CFRP-CFFT UHPFRC columns subjected to axial load with a varying eccentricity.